2011
DOI: 10.1116/1.3525882
|View full text |Cite
|
Sign up to set email alerts
|

Temperature threshold for nanorod structuring of metal and oxide films grown by glancing angle deposition

Abstract: Thin films of tin (Sn), aluminum (Al), gold (Au), ruthenium (Ru), tungsten (W), ruthenium dioxide (RuO2), tin dioxide (SnO2), and tungsten trioxide (WO3) were grown by glancing angle deposition (GLAD) to determine the nanostructuring temperature threshold, ΘT, above which adatom surface diffusion becomes large enough such that nanorod morphology is no longer formed during growth. The threshold was found to be lower in metals compared to oxides. Films were grown using both dc and pulsed dc magnetron sputtering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…In Zone T, thin films deposited with a normal configuration possess a microstructure formed by perpendicular and compacted columnar grains that are thicker than those produced in Zone I. Similarly, heating the substrate during OAD produces a change in microstructure due to an increase in the mobility of ad-particles [49]. One way of rationalizing these nanostructural changes is to assume that dominance of shadowing in controlling the film growth is partially reduced by the diffusion of ad-particles from their point of impact to otherwise inaccessible ''shadowed" regions.…”
Section: Effects Of Temperature and Deposition Rate On The Morphologymentioning
confidence: 93%
See 3 more Smart Citations
“…In Zone T, thin films deposited with a normal configuration possess a microstructure formed by perpendicular and compacted columnar grains that are thicker than those produced in Zone I. Similarly, heating the substrate during OAD produces a change in microstructure due to an increase in the mobility of ad-particles [49]. One way of rationalizing these nanostructural changes is to assume that dominance of shadowing in controlling the film growth is partially reduced by the diffusion of ad-particles from their point of impact to otherwise inaccessible ''shadowed" regions.…”
Section: Effects Of Temperature and Deposition Rate On The Morphologymentioning
confidence: 93%
“…Nevertheless, in a systematic investigation of the OAD of magnetic metals and alloys (Co, Ni, Fe), Hara et al [51][52][53][54][55][56] showed that although the aforementioned relation between temperature and deposition rate was generally maintained, other effects besides diffusion must be involved to explain unexpected deviations in the growth tendencies and the appearance of more complex morphological patterns. For a large variety of metals and oxides deposited by DC magnetron sputtering, Deniz et al [49] determined the nanostructuration Cross sectional SEM images of (a) zig-zag nanocolumns obtained by back and forth azimuthal turning of the substrate [63], (b) spiral nanocolumns obtained by continuous azimuthal rotation (i.e., dynamic OAD) [87], (c) zig-zag plus spiral nanocolumns (author's unpublished results), (d) nanocolumns with width modulation obtained by azimuthal rotation and back and forth polar angle tilting [87], and (e) vertical nanocolumns obtained by rapid azimuthal rotation at two different rates [65]. above which ad-atom surface diffusion becomes dominant over surface shadowing, thereby preventing the formation of a typical OAD nanocolumnar morphology. For metals, this temperature threshold has been tentatively established at around 0:33T f , while for oxides the value is approximately 0:5T f .…”
Section: Effects Of Temperature and Deposition Rate On The Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…5,15 This temperature range shows a good agreement with the experimental results of GLAD and it was observed that almost none or very poor columnar growth occurs for metallic films above this temperature range. [16][17][18][19][20][21] It is really interesting to probe that whether the columnar growth persists throughout this zone 1 even when the substrate temperatures goes down to liquid nitrogen. In an interesting research by Hara et al, they observed a non-monotonic variation in the inclination angle of columnar grains when the homologous temperature get reduced to a value less than 0.1 during deposition of Fe at an oblique angle of 60 .…”
Section: Introductionmentioning
confidence: 98%